Information Security Maintenance Issues for Big Data - Sergey Vladimirovich Zapechnikov; Natalia Georgievna Miloslavskaya; Mikhail Yurievich Senatorov; Aleksandr Ivanovich Tolstoy (Безопасность информационных технологий, 2014)
The main big data technologies are briefly listed. The need to protect such data, particularly those relating to information security (IS) maintenance of an enterprise’s IT infrastructure, and their processing processes is shown. A worldwide experience of addressing big data IS issues is briefly summarized. A big data protection problem statement is formulated. An infrastructure for big data information security maintenance is offered. New applications areas for big data IT after addressing IS maintenance issues for them are listed in conсlusion.